The greener, the better? Evidence from government contractors - Olga Chiappinelli; Ambrogio Dalò; Leonardo M. Giuffrida (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2024)
Governments can support the green transition through green public procurement. Despite its strategic importance, the impact of this policy on firms remains unclear. Using US data, this paper provides the first empirical analysis of the causal effects of green contracts on corporate environmental and economic performance. We focus on an affirmative program for sustainable products, which represents one-sixth of the total federal procurement budget, and publicly traded firms, which account for one-third of total US emissions. Our results show that securing green contracts reduces emissions relative to firm size and increases productivity, with these effects persisting in the long run. We find no evidence that the program selects greener firms, nor that green public procurement sales crowd out private sales. We propose that increased R&D investment, incentivized by the program's requirements, is a key mechanism behind these improvements.
Keywords: D22; D44; H32; H57; Q53; Q54; Q58; 330; Public Procurement; Environmental Policy; Firm Performance; Greenhouse Gas Emissions; R&D; Recycled materials; Staggered Difference-in-difference